Numerical analysis of hydrothermal flow and heat transfer inside a cavity formed due to faults causing earthquakes - Nadeem, Sohail; Akber, Rehan; Almutairi, Shahah; Ghazwani, Hassan Ali; Mahmoud, Omar (Frontiers in Physics, 2022)
This article studies fluid dynamics and convection of geothermal system. Earthquakes cause faults. Fault zones come up with the pathways for fluid convection. These paths have different characteristics and space distribution causing a challenge to investigate the geothermal system. The cavity considered in the study is normally found in the energy reservoirs. An unsteady, incompressible and laminar flow along with convection is studied. Finite element method (FEM) is operated to study the flow and heat transfer governed by continuity equations, Navier-Stokes equations and temperature equations. These equations are tackled by finite element method. The streamlines and isothermal contours for under discussion problem are displayed in the results section. It is observed that Nusselt number and velocity of the fluid increase with the increased Grashof number.